Leadership for learning: The relationships between school context, principal leadership and mediating variables. Issue 2 (13th March 2017) - Paletta, Angelo; Alivernini, Fabio; Manganelli, Sara
Abstract : Purpose: The purpose of this paper is to examine the relationships between the school context, the leadership of the school principal, and a set of process variables related to teachers and the educational climate, which have been shown to mediate the effects of the principal's leadership on schools and students. The authors examined the following research questions: does the school context influence the principal's leadership? When the influences of the school context are controlled for, does the principal's leadership influence the process variables related to teachers and educational climate? Design/methodology/approach: The research questions are analysed in a multilevel context by developing two models regarding the hypothesized relationships between the study variables. With the use of multilevel structural equation modelling techniques the models were empirically tested on data from Italian teachers and students from a sample of schools in Italy. The database include 1, 566 teachers from 47 schools of different types and levels from the Autonomous Province of Trento. Findings: In those schools which have the highest leadership scores, the authors also find a greater degree of job satisfaction among the teachers, higher levels of self-efficacy of teachers, and a better educational climate, which is more respectful of the basic rules of coexistence existing within the school. An interesting additional element is that the positive relationship between the exercise of leadership and the process variables related to academic success is still present, even if the effects of the school context are controlled for. Research limitations/implications: It should be observed that the results of this study, particularly due to the non-representative nature of the sample considered, should be considered as preliminary evidence that will require further confirmation, and which cannot be immediately generalized. The results obtained can be influenced by the specific territorial area in which this search has been conducted. The Autonomous Province of Trento, from the rest of Italy, is characterized by a highly centralized education system, with a relative homogeneity of the conditions of the context in which schools have achieved so widespread high levels of student learning. Originality/value: When studying leadership it is important to consider the school context, particularly the role of the initial level of learning of the students, as this study shows that in schools where the prior knowledge of students is greater, teachers are generally more satisfied with their job and they report a better educational environment. If the influence of the context were not taken into account, this could easily be mistaken for that of the actions of the principal.